2010
DOI: 10.1038/ajh.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Collagen Synthesis and Degradation and Aortic Function in Arterial Hypertension

Abstract: Alterations in collagen turnover that favor collagen type I synthesis; as well as proMMP-1 expression are related to increased aortic stiffness in treated hypertensive individuals without left ventricular (LV) hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
5
32
1
3
Order By: Relevance
“…In two studies, data of hypertensive patients were combined [28,39]. Five studies provided plasma MMP-1 levels [21,31,32,35,40]; the SMD between 305 hypertensive patients and 323 controls was 0 units [95% confidence interval (CI) À1.48, 1.48], not statistically significant. Sensitivity analysis excluding the studies with different mean age between groups and the studies in which age was not stated provided similar results.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, data of hypertensive patients were combined [28,39]. Five studies provided plasma MMP-1 levels [21,31,32,35,40]; the SMD between 305 hypertensive patients and 323 controls was 0 units [95% confidence interval (CI) À1.48, 1.48], not statistically significant. Sensitivity analysis excluding the studies with different mean age between groups and the studies in which age was not stated provided similar results.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, alterations in collagen turnover that favor type I collagen synthesis are also related to a decreased aortic elasticity 47,48 . Fibrillar type I/III collagens are the most abundant in vascular walls 49 and they play an important contribution to the rigidity of the arterial wall of resistance arteries in hypertension 6,9,31,50 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies in humans evaluating the levels of MMPs and ADAMs in the systemic circulation during hypertension and left ventricular hypertrophy, as well as heart failure [84,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130]. A meta-analysis of these studies concluded that elevation of MMP-2 and MMP-9 can be used as plasma biomarkers for cardiovascular remodeling in hypertension [131].…”
Section: Mmps and Adams In Human Hypertensive Cardiac Diseasementioning
confidence: 99%